2012
DOI: 10.1002/jcb.23379
|View full text |Cite
|
Sign up to set email alerts
|

Cellular distribution of Glut‐1 and Glut‐5 in benign and malignant human prostate tissue

Abstract: Over-expression of hexose transporters (Gluts), specifically Glut-1, is a common event in human malignancies. In prostate cancer (CaP), however, expression of Gluts has been characterized poorly. In this study, expression and distribution of Glut-1 and Glut-5 proteins were characterized using immunohistochemistry in 76 specimens of benign prostate, 10 specimens of high-grade intraepithelial neoplasia (HGPIN), and 28 specimens of CaP. In addition, mRNA expression of Glut-2, Glut-7, Glut-9, and Glut-11 was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 46 publications
1
79
0
1
Order By: Relevance
“…This is further in agreement with cell line studies, which show that the metastastic androgen-sensitive cell line LNCaP and the castration-resistant low-differentiation cell lines DU-145 and PC-3 are sensitive to glucose starvation [152] and that androgen signaling enhances the expression of glycolytic enzymes [161][162][163]. However, whether or not an increased expression of the glucose transporter 1 or other hexose transporters are causal for this phenotype is still a matter of debate, since histological data are inconclusive [164][165][166][167].…”
Section: Later Stage Prostate Cancer Metabolismsupporting
confidence: 82%
“…This is further in agreement with cell line studies, which show that the metastastic androgen-sensitive cell line LNCaP and the castration-resistant low-differentiation cell lines DU-145 and PC-3 are sensitive to glucose starvation [152] and that androgen signaling enhances the expression of glycolytic enzymes [161][162][163]. However, whether or not an increased expression of the glucose transporter 1 or other hexose transporters are causal for this phenotype is still a matter of debate, since histological data are inconclusive [164][165][166][167].…”
Section: Later Stage Prostate Cancer Metabolismsupporting
confidence: 82%
“…In addition, GLUT-1 was undetectable in high-grade prostatic intraepithelial neoplasia and prostate cancer. These results suggest that carcinogenesis in prostate tissue is not associated with GLUT-1 expression, and therefore that glucose might not play an important role in maintaining prostate cancer cell metabolism (Reinicke et al, 2012). Consistent with this, an additional study examined resected prostate cancer tissues immunohistochemically using anti-GLUT-1 antibodies, and revealed only weak positive staining.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, they reported that FDG accumulation was not related to clinical stage or histological grade. The study by Effert et al used continuous bladder irrigation with a Foley catheter to reduce the artifacts caused by residual urinary activity; however, this did not result in increased tumor uptake (Effert et al, 1996;Reinicke et al, 2012). This result could be explained by reports that prostate cancer uses hexoses other than glucose, such as fructose, preferentially.…”
Section: Discussionmentioning
confidence: 99%
“…[124,125]. An enhanced expression of GLUT1 is found in prostate carcinoma cells, which includes a novel co-localisation of GLUT1 with a Golgi marker.…”
Section: F]fdg Is Therefore An Excellentmentioning
confidence: 98%